2010
DOI: 10.1124/dmd.110.032813
|View full text |Cite
|
Sign up to set email alerts
|

Reduction ofN-Hydroxy-sulfonamides, IncludingN-Hydroxy-valdecoxib, by the Molybdenum-Containing Enzyme mARC

Abstract: ABSTRACT:Purification of the mitochondrial enzyme responsible for reduction of N-hydroxylated amidine prodrugs led to the identification of two newly discovered mammalian molybdenum-containing proteins, the mitochondrial amidoxime reducing components mARC-1 and mARC-2 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…With the exception of the human Moco sulfurase HMCS, which is required for activating the Mo-enzymes AO and XOR (9) and which is the name-giving member of the MOSC family, no other homolog of hmARC-1 and hmARC-2 is found in the human genome. Cloning of hmARC-1 and hmARC-2 cDNAs derived from HepG2 cells (16,17) basically confirmed the predicted sequences of the protein-encoding open reading frames as deposited in the database, with the exception of two reproducible polymorphisms that were identified in the hmARC-1 cDNA causing substitutions of methionine 187 by lysine (protein entry NP_073583 versus AAH10619) and alanine 165 by threonine (protein entry ACB21046 versus NP_073583).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…With the exception of the human Moco sulfurase HMCS, which is required for activating the Mo-enzymes AO and XOR (9) and which is the name-giving member of the MOSC family, no other homolog of hmARC-1 and hmARC-2 is found in the human genome. Cloning of hmARC-1 and hmARC-2 cDNAs derived from HepG2 cells (16,17) basically confirmed the predicted sequences of the protein-encoding open reading frames as deposited in the database, with the exception of two reproducible polymorphisms that were identified in the hmARC-1 cDNA causing substitutions of methionine 187 by lysine (protein entry NP_073583 versus AAH10619) and alanine 165 by threonine (protein entry ACB21046 versus NP_073583).…”
Section: Resultsmentioning
confidence: 93%
“…Construction of Expression Vectors-Full-length cDNAs of hmARC-1 (1011 base pairs corresponding to NCBI reference sequence NM_022746, MOSC-1) and hmARC-2 (1005 base pairs corresponding to NCBI reference sequence NM_017898, MOSC-2) were obtained as described earlier (15)(16)(17). For cloning of N-terminally truncated hmARC-1, the full-length open reading frame was truncated at its 5Ј end by PCR using the primers hmARC-1_Start_N-del (5Ј-ATA TAT GGA TCC ATG CAG CAG GTG GGC ACA GTG GCG-3Ј) and hmARC1_Stop (5Ј-AAA TTT AAG CTT TTA CTG GCC CAG CAG GTA CAC AGG-3Ј).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of this reduction has been extensively studied. Cytochrome b5 and its reductase and several molybdenumcontaining enzymes such as aldehyde oxidase were all capable of carrying out the reduction (Vonk et al, 1986;Saulter et al, 2005;Havemeyer et al, 2010). Sugihara et al (2000) also reported nonenzymatic N-dehydroxylation by hemoglobin under anaerobic conditions.…”
Section: Discussionmentioning
confidence: 99%